The New Institutional Architecture of Eastern Europe - Whitefield, Stephen. author. aut Link
IX, 204 p.
Keywords: The book is concerned with the formation of new institutions in Eastern Europe following the events of 1989. Two comparative chapters discuss the problems of institution building arising from the communist legacy and the difficulties of a successful transition to liberal democracy. In the remainder of the book, country-specific chapters deal with the institutional characteristics of countries in the region - Yugoslavia, Czechoslovakia, Poland, Hungary, Bulgaria, Romania, Russia, East Germany. Attention is focused on constitutions, executive and parliament relations, and parties and electoral systems.